On one class of symmetric Boolean functions - Zhi-hui OU; Ya-qun ZHAO (Tongxin xuebao)
The properties of one class of symmetric Boolean funct which was denoted by Â was discussed,a different method for proving that one subclass of Â having maximum algebraic immunity was presented.A necessary condition was proposed for the functions of Â with maximum algebraic immunity,of which a lower bound of the number was also given.Meanwhile,the algebraic degree of most functions of Â was determined and linear structure and correlation immunity of Â were also analyzed.The results show that the functions of Â have no non-zero linear structure and only two functions of Â have 1-correlation immunity.